Optimalisasi Pemanfaatan Toga dalam Meningkatkan Kemandirian Kesehatan Masyarakat di Desa Klagensrampat Kabupaten Lamongan - Fita Fitriatul Wahidah; Adam Pratama Septian; Sitti Nur Ilmiah; Rahmah Arfiyah Ula; Lilik Erviani; Merinda Nur Indahsari (Fakultas Teknik Universitas Cenderawasih, 2025)
One of the Lamongan Regency government programs related to family medicinal plants (TOGA) is Asman Toga (Independent Care of Family Medicinal Plants). This program is one of the Lamongan Regency Government's efforts to reduce stunting rates. One of the villages that already has Asman Toga is Klagensrampat Village. The outreach aims to provide knowledge to the public, especially regarding the benefits of plants against types of diseases and how to treat Toga, as well as how to independently process Toga into ready-to-eat medicine (either in the form of drinks, rhizomes or powder). Service activities are carried out in the form of direct outreach to the Klagensrampat Village community. Before and after the socialization was carried out there were pre-tests and post-tests carried out by the participants. Evaluation activities carried out to assess public knowledge about the use of Family Medicinal Plants (TOGA) were carried out with written exams in the form of pre-tests and post-tests. The results of the analysis show that there has been an increase in public knowledge about the benefits of Toga for various minor illnesses.